The Impact of Organisational Structure on Project Performance in the Energy Sector - Basioni, Ahmed (2024)
Purpose – The objective is to explore the impact of organisational structure on project performance and current research topics regarding organisational structure theories, types, and aspects in terms of challenges, culture, communication, organisational dynamics, and drivers. Methodology – The adopted methodology employs two integrated approaches. First, use a systematic mapping approach to explore the existing research studies on organisational structure’s impact. Second, correlate the research studies to existing case studies in the energy sector, record findings, and propose recommendations on the way forward. Findings – The study results concluded that most oil producers are a mix of functional and matrix organisations with diversified thoughts on centralizing project management teams. Implications/limitations – It is essential to conduct follow-up research validating the potential for using the findings of this study to establish frameworks for the organisational transformation approach in meeting cultural variance and market conditions. Originality/value – The proposed case studies and relevant theories present the most effective organisational structure model to improve project-based operations performance, thus enabling oil and gas organisations to manage their business mandates effectively.